Prediction of Car Ground Clearance - Zamri, Mohamed; Mohd Redza, Abdul Razak (2009)
Abstract— In layout drawing, one of the basic components that it must have is the estimation of ground lines that will enable engineers to measure the clearance of car components especially the lower part to ground. This paper explains how to formulate simple equations in order to estimate the location of ground lines by taking into account the suspension characteristics of the car as well as three cases of weight loadings. Furthermore a program is written in assembly language in order to ease engineers in getting the ground lines coordinates at specific loadings. The result of program calculation will provide the estimation of the wheel centers as well as the ground lines. In the modeling, car body is placed as static whereas the ground lines moves vertically. Of course in real case the vice versa happens, however this method is unavoidable since in car drawing, one does not want to move the car drawing from its datum due to its dependability to the datum of other components. The result from the wheel center coordinates and the ground lines location will enable engineer to estimate the displacement of spring and at the same time the vertical deformation of tire. In conclusion, this method of ground lines will help design engineers or packaging engineers in automotive development company to speed up the layout making and hence will minimize costly error later at development stage.